What to Learn? Socialization of the Subject Hierarchy in Schools. Issue 1 (2nd January 2021) - Araneda, Daniel; Galarce, Jeremy; Alvares, Danilo; Nussbaum, Miguel
Abstract: The role of the school curriculum is in tension with two points: socializing the essential knowledge needed for life and reflecting the inequalities of society. The present study looks at the effectiveness of this socialization by comparing learner interests with the national curriculum. 442 10th grade students in Chile were divided into 4 groups based on their socioeconomic status and academic achievement. The students were asked to design two ideal school timetables: one reflecting their interests, and one showing what they feel is relevant for their future. The results reveal that student interests differ considerably from the national curriculum. However, when students design a timetable based on their future it tends to resemble the curriculum much more closely. Socioeconomic status proved not to be particularly relevant. On the other hand, gender appears to be the most significant variable when explaining these differences.